Monitoring Adolescent Mobile Application (MAMA) Using GPS-Assisted Location Services / Muhammad Ikmal Rozzaman - Rozzaman, Muhammad Ikmal (2017)
This project is about Mobile Application Development of Monitoring Adolescent Mobile Application (MAMA) using GPS-Assisted Location Services. Data gathering done through observation and survey on stakeholder which are parents and adolescent. It has been discovered that most parents in Malaysia usually are working and face a hard time monitoring their adolescent location due to busy with work, so not all time they can monitor their adolescent location when they are outside. Besides that, the adolescent abduction cases are continuously increasing. This is particularly worrying parents to allow their adolescent out of the house. These is also a risk factor for the parent in child abduction because there‟s no decent method to minimize the issue. Normally parents use a social media application as a method for tracking and monitoring their adolescent. From these findings, it clearly shows that most parents in Malaysia currently does not have a very good method for monitoring their adolescent. Thus, this project is planned to develop a mobile application that provides some features which include location tracking, group, chat group, private message, geofence, help alert and other more features. There are four (4) phases in order to achieve these objectives. Phases of this project are planning and requirements gathering, analysis, design, and development. The raw data obtained from those requirements gathering technique was analyzed using CRUD analysis technique. A list of use cases was produced and be visualized using UML diagrams. The use cases and domain class diagram were documented in the Software Requirement Specification (SRS). While the system design and structures were documented in the Software Design Documentation (SDD). From this project, it will benefit the parent and adolescent in Malaysia in terms of monitoring their adolescent using this application. The future recommendation for the project are improves the security, available for other platform, adding push notification for other features and make available on offline help alert.